High-yield synthesis of HMF from glucose and fructose by selective catalysis with water-tolerant rare earth metal triflates assisted by choline chloride. Issue 4 (8th February 2023) - Olivito, Fabrizio; Algieri, Vincenzo; Tallarida, Matteo Antonio; Jiritano, Antonio; Costanzo, Paola; Maiuolo, Loredana; Nino, Antonio De
Abstract : Hydroxymethylfurfural (HMF) derived from sugars through an environmentally friendly process catalysed by metal triflate/choline chloride system is presented in this study. Abstract : The conversion of naturally occurring organic substances into value-added platform chemicals by simple, green, and efficient procedures represents one of the most accessible and sought-after routes towards sustainable chemistry. In the present work, we report the remarkable catalytic activity of rare-earth metal triflates in conjunction with choline chloride, a natural, low-cost, and available organic compound to selectively convert glucose and fructose into hydroxymethylfurfural (HMF). The hypothesized mechanism is based on the initial glycosylation of glucose assisted by scandium(iii ) triflate and choline chloride to produce a glycoside, which can evolve through an intramolecular rearrangement and subsequent dehydration to produce the final product HMF. A comparison with other types of catalysts is carried out with particular focus on the side reactions. The apparatus consists of a closed biphasic system and the excellent capacity of methyl propyl ketone (MPK) to extract HMF in only one cycle is proved. The process was conducted at 150 °C using 1.5 molar equivalents of choline chloride in which glucose was converted into HMF after three hours using the catalyst in 8% molar quantity, while fructose was converted in one hour employing the catalyst in 4% molar quantity. The best performance was obtained by employing scandium(iii ) triflate as a catalyst with an yield of 94% and 99% of HMF from glucose or fructose, respectively. We assumed a first-order reaction model for both glucose and fructose conversion into HMF. The R-squared values are greater than 0.9, demonstrating that our kinetic model fitted well with the experimental results. In addition, activation energies are 16.9 kJ mol −1 for glucose and 9.31 kJ mol −1 for fructose due to the longer reaction path of glucose. The catalytic system can be recycled up to five times with a HMF yield of over 80% for glucose and over 90% for fructose, maintaining the same selectivity.